Deep eutectic solvents (DES) mediated extraction of pectin from Averrhoa bilimbi: Optimization and characterization studies. (15th July 2019) - Shafie, Muhammad Hakimin; Yusof, Rizana; Gan, Chee-Yuen
Highlights: DES is a potential extraction medium. A HM acidic pectin was produced and its properties were characterized. The optimum pectin yield from A. bilimbi was 14.44%. ABP has exhibited significant antioxidant activities. Abstract: The Box–Behnken design was applied to optimize the extraction of pectin from Averrhoa bilimbi (ABP) using deep eutectic solvents (DES). The four variables of extraction were percentage of DES ( X 1 ), extraction time ( X 2 ), temperature ( X 3 ), and molar ratio of DES components ( X 4 ). The quadratic regression equation was established as a predicted model with R 2 value of 0.9375. The optimal condition was X 1  = 3.74% (w/v), X 2  = 2.5 h, X 3  = 80 °C, and X 4  = 1:1. No significant difference between the predicted (14.70%) and experimental (14.44%) maximum yield of sample was noted. Characterization of physico-chemical properties characterization of ABP was performed. The main components of ABP were galacturonic acids, arabinoses, and xyloses. ABP also showed good functional properties such as water holding capacity (3.70 g/g), oil holding capacity (2.40 g/g), and foaming capacity (133.33%). The results also showed that ABP exhibited free radical scavenging activity (41.46%) and ferric reducing antioxidant power (1.15 mM).